Outcomes and Quality of Life Improvement After Multilevel Spinal Fusion in Elderly Patients. Issue 2 (April 2020) - Ibrahim, John M.; Singh, Paramjit; Beckerman, Daniel; Hu, Serena S.; Tay, Bobby; Deviren, Vedat; Burch, Shane; Berven, Sigurd H.
Study Design: Retrospective case series. Objectives: Both the rate and complexity of spine surgeries in elderly patients has increased. This study reports the outcomes of multilevel spine fusion in elderly patients and provides evidence on the appropriateness of complex surgery in elderly patients. Methods: We identified 101 patients older than70 years who had ≥5 levels of fusion. Demographic, medical, and surgical data, and change between preoperative and >500 days postoperative health survey scores were collected. Health surveys were visual analogue scale (VAS), EuroQoL 5 Dimensions (EQ-5D), Oswestry Disability Index (ODI), Scoliosis Research Society questionnaire (SRS-30), and Short Form health survey (SF-12) (physical composite score [PCS] and mental composite score [MCS]). Minimal clinically important differences (MCIDs) were defined for each survey. Results: Complications included dural tears (19%), intensive care unit admission (48%), revision surgery within 2 to 5 years (24%), and death within 2 to 5 years (16%). The percentage of patients who reported an improvement in health-related quality of life (HRQOL) of at least an MCID was: VAS Back 69%; EQ-5D 41%; ODI 58%; SRS-30 45%; SF-12 PCS 44%; and SF-12 MCS 48%. Improvement after a primary surgery, as compared with a revision, was on average 13 points higher in ODI ( P = .007). Patients who developed a surgical complication averaged an improvement 11 points lower on ODI ( P = .042). Patients were more likely to find improvement in their health if they had a lower American Society of Anesthesiologists or Charlson Comorbidity Index score or a higher metabolic equivalent score. Conclusions: In multilevel surgery in patients older than 70 years, complications are common, and on average 77% of patients attain some improvement, with 51% reaching an MCID. Physiological status is a stronger predictor of outcomes than chronological age.